Electrophysiological characteristics and catheter ablation of symptomatic focal premature atrial contractions originating from pulmonary veins and non‐pulmonary veins. Issue 1 (25th January 2018) - Huang, Xingfu; Chen, Yanjia; Xiao, Junhui; Zhao, Hongxin; Chen, Yizhen; Liu, Shenrong; He, Liwei; Huang, Zheng; Zhou, Haobin; Xu, Dingli; Peng, Jian
Abstract : Background: We aimed to explore electrophysiological characteristics of premature atrial contractions (PACs) originating from pulmonary veins (PVs) and non‐PVs and to evaluate the effectiveness and safety of catheter ablation for PACs. Hypothesis: Symptomatic PACs originated from different positions and whether could be ablated. Methods: Symptomatic, frequent, and drug‐refractory PAC patients were enrolled in this study. All patients underwent electrophysiological study and catheter ablation. Results: A total of 81 patients were enrolled: 45 patients with PACs originating from PVs (group A), 24 patients with PACs originating from non‐PVs (group B), and 12 patients with PACs arising from both PVs and non‐PVs (group C). Twenty (44.4%) patients in group A, 6 (50.0%) patients in group C, and 3 (12.5%) patients in group B presented paroxysmal atrial fibrillation ( P  < 0.05). PV isolation was performed in groups A and C. Focal ablation or superior vena cava isolation was performed in groups B and C, depending on patient condition. PACs were abolished in all patients except one patient in group B. During a median follow‐up period of 21.3 ± 14.3 months, 40 (88.9%) patients in group A, 10 (83.3%) patients in group C, and 21 (87.5%) patients in group B were free of recurrence after initial ablation. Conclusions: Frequent PACs originating from PVs were associated with increased incidence of atrial fibrillation compared with PACs originating from non‐PVs. Catheter ablation yields a satisfactory success rate and could be a good choice for eliminating symptomatic, frequent, and drug‐refractory PACs.